230k views
0 votes
What is -3(4r - 8) = -36

User Haelin
by
5.1k points

2 Answers

2 votes

Answer:

-3(4r-8)=-36

-3 ×4r = -12r

(Negative and positive equals negative)

-3×-8= 24

(Both negatives equal positive)

-12r+24=-36

(-24 to like terms. Meaning, just subtract 24 from the -36 and the 24

Leave change change uwo)

-36-(-24) is now -36 + 24= -12

-12/-12r= -12/-12

r=1

This actually helped me with a problem i had to do "x can be any number" so thenk lol

User Adam Gritt
by
5.0k points
3 votes

-3(4r - 8) = -36

Mutiply the bracket by -3

(-3)(4r)(-3)(-8)= -12r+24

-12r+24= -36

move +24 to the other side

sign changes from +24 to -24

-12r+24-24= -36-24

-12r= -60

divide by -12

-12r/-12= -60/-12

r= 5

Answer: r= 5

User Elyana
by
5.1k points